G128(P) 'Assessment to treat rather than admission to assess': establishing a permanent paediatric assessment unit at a district general hospital. (25th October 2020) - Modgil, G; Whiting, A; Pilkington, S; Jackson, C; Peters, H; Bryant, M; Baum, R; Knight, A
Abstract : Aim: A quality improvement Paediatric Assessment Unit (PAU) pilot creating a consistent model of 'assessment to treat' rather than 'admission to assess'. To establish a permanent PAU at a district general hospital (DGH). Specific aims included improving quality of care, reducing unnecessary admissions, improving patient experience, increasing primary care access to senior advice and bringing paediatrics services in line with an 'integrated front door' approach. Method: Historically, paediatric assessments and admissions had the same care pathway at our DGH. Local CCG analysis indicated that children were twice as likely to be admitted compared to other regional units with separate PAU facilities. A funded 3 month pilot PAU ran from January- April 2019. The pilot ensured that senior decision making took place at the point of referral, triage and review. Results: 434 children attended during this time. Of these, 122 children were assessed and subsequently admitted (28%) and 312 were treated and allowed home (72%). Proportion of patients waiting to receive a clinical decision greater than 120 minutes fell from 46% to 10%, with significantly more children receiving a clinical decision within 60 minutes, exceeding RCPCH standards. Improved advice to primary care: 31% calls given specialist advice, decreasing admission/referrals to outpatients. Consultant Connect answer rates increased from 54% to 83%, with 56% patients avoiding an unnecessary visit to hospital. 100% children screened for sepsis with significant improvements for children requiring antibiotics within one hour. There were less reported patient/carer concerns with positive patient experience. Staff experience was universally positive with improved working environment, structure and morale. Trainee exception reporting reduced. GMC Trainee Survey results improved by two quartile positive shift for workload: highlighting good team work and supportive working environments. This model supported achievement of Standard 2 'Facing the Future' standards and was recognised in the NHSI cross county review of paediatric services. Conclusion: The qualitative and quantitative outcomes were presented to our Trust, A&E delivery board and the STP business planning teams. The business case was successfully supported for funding a permanent PAU from January 2020. A PAU alongside ED remains the long term ambition for an integrated front door/acute paediatric assessment hub.